Desmoplastic tumor priming using clinical-stage corticosteroid liposomes - Ojha, Tarun; Schaefer, Gideon J L; Mihyar, Rahaf; Pathak, Vertika; Ehling, Josef; Rama, Elena; De Lorenzi, Federica; Elshafei, Asmaa Said; Moeckel, Diana; Elsafy, Sara; Theek, Benjamin; Wagner, Maike; et al. (Cell biomaterials, 2025)
Inflammation is a hallmark of cancer. It contributes to a heterogeneous, hyperpermeable, and poorly perfused tumor vasculature, as well as to a dense and disorganized extracellular matrix, which together negatively affect drug delivery. Reasoning that glucocorticoids have pleiotropic effects, we use clinical-stage dexamethasone liposomes (LipoDex) to prime the tumor microenvironment for improved drug delivery and enhanced treatment efficacy. We show that LipoDex priming improves tumor vascular function and reduces extracellular matrix deposition. Single-cell sequencing corroborates LipoDex-mediated inhibition of pro-inflammatory, pro-angiogenic, and pro-fibrogenic gene expression in mononuclear cells, tumor-associated macrophages, and cancer-associated fibroblasts. Multimodal optical imaging illustrates that LipoDex pre-treatment increases the tumor accumulation and intratumoral distribution of subsequently administered polymeric and liposomal drug delivery systems. Using Doxil as a prototypic nanodrug, we finally show that LipoDex priming promotes antitumor treatment efficacy. Altogether, our findings demonstrate that desmoplastic tumors can be primed for improved drug targeting and therapy using clinical-stage glucocorticoid liposomes.
Keywords: tumor priming; drug targeting; corticosteroids; liposomes; tumor-associated macrophages; nanomedicine; cancer-associated fibroblasts; tumor microenvironment